Trial summary and protocol for a phase II randomised placebo-controlled double-blinded trial of Interleukin 1 blockade in Acute Severe Colitis: the IASO trial. Issue 2 (15th February 2019) - Thomas, Martin Geoffrey; Bayliss, Carrie; Bond, Simon; Dowling, Francis; Galea, James; Jairath, Vipul; Lamb, Christopher; Probert, Christopher; Timperley-Preece, Elizabeth; Watson, Alastair; Whitehead, Lynne; Williams, John G; et al.
Abstract : Introduction: Acute severe ulcerative colitis (ASUC) is a severe manifestation of ulcerative colitis (UC) that warrants hospitalisation. Despite significant advances in therapeutic options for UC and in the medical management of steroid-refractory ASUC, the initial treatment paradigm has not changed since 1955 and is based on the use of intravenous corticosteroids. This treatment is successful in approximately 50% of patients but failure of this and subsequent medical therapy still occurs, with colectomy rates of up to 40% reported. The I nterleukin 1 (IL-1) blockade in A cute S evere Co litis (IASO) trial aims to investigate whether antagonism of IL-1 signalling using anakinra in addition to intravenous corticosteroid treatment can improve outcomes in patients with ASUC. Methods and analysis: IASO is a phase II, multicentre, two-arm (parallel group), randomised (1:1), placebo-controlled, double-blinded trial of short-duration anakinra in ASUC. Its primary outcome will be the incidence of medical (eg, infliximab/ciclosporin) or surgical rescue therapy (colectomy) within 10 days following the commencement of intravenous corticosteroid therapy. Secondary outcomes will include disease activity, time to clinical response, time to rescue therapy, colectomy incidence by day 98 post intravenous corticosteroids and safety. The trial aims to recruit 214 patients across 20 sites in the UK. Ethics and dissemination: The trial has received approval from the Cambridge Central Research Ethics Committee (Ref: 17/EE/0347), the Health Research Authority (Ref: 201505) and Clinical Trials Authorisation from the Medicines and Healthcare products Regulatory Agency. We plan to present trial findings at scientific conferences and publish in high-impact peer-reviewed journals. Trial registration number: ISRCTN43717130 ; EudraCT 2017-001389-10.